Governance of Village Fund Allocation in Empowering Citizens - Zulmasyhur Zulmasyhur (Budapest International Research and Critics University, 2022)
The Indonesian government's strategy to develop villages to become independent and autonomous is by distributing Village Fund Allocations (ADD). The purpose of this study is to describe the governance of Village Fund Allocation in empowering citizens with the exploration of driving and inhibiting aspects. The research method used is descriptive qualitative. The results of the study showed that some of the ADD funds for community empowerment were used for the operational costs in the village government and the BPD. Thus, the use of the Village Fund Allocation is not in accordance with what it should be. The supporting aspect in managing the Village Fund Allocation is citizen participation. However, the inhibiting aspect lies in the quality of human energy resources and the lack of direct supervision from residents.